The Influence of Marketing Communications, Experience and Quality of Services on Image and Satisfaction, Their Impact on Tourist Loyalty of the Nusantara (Survey of Waterfall Recreational Places in Malang District) - Askar Jaya; Deltri Apriyeni; Romi Susanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The study aims to get an overview of marketing communications, experience and quality of services as the cause of image formation and satisfaction and its impact on loyalty of domestic tourists in the waterfall recreation area. The object of this research is waterfalls in Malang, namely Curug Bidadari and Curug Nangka. The number of samples acceptable in this study is 50 respondents. This number is a critical sample size in the sample measurements required through SEM Partial Least Square (PLS). From the questionnaires distributed on both waterfalls, collected 114 complete questionnaires that can be processed. The data analyzed in this research using Partial Least Square (PLS) method and using Smart PLS tools. The results showed that marketing communications significantly related to the image. This shows that interesting communication will form a positive image and encourage tourists to visit. Compared with marketing communications, experience has more role in shaping the image of the place of recreation. Service quality is significantly related to image. Service quality has the most dominant effect on image over experience and communication. Service quality is significantly related to satisfaction. Service quality is not significantly related to loyalty. The image is significantly related to satisfaction. The image is not significantly related to loyalty. Although the image does not directly affect the loyalty, but the image has an indirect effect on loyalty through satisfaction. Satisfaction is significantly related to loyalty. Of all the variables that have influence on loyalty the biggest influence is the variable of respondent satisfaction, that is the promotion of this recreation place as a place of recreation.